PENGARUH PEMBELAJARAN BERBASIS PRAKTIKUM TERHADAP EFEKTIVITAS PEMBELAJARAN MAHASISWA AKUNTANSI UNISMA - Ahmad Dani Dzakiyuddin; Nur Hidayati; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACT This research was conducted to analyze "The Effect of Practicum Based Learning Against the Effectiveness of UNISMA Accounting Student Learning". The population in this study is the Accounting Students of the Faculty of Economics and Business, Islamic University of Malang. The samples in this study are students of class 2019 - 2020 Faculty of Economics and Business Accounting Study Program Malang Islamic University and students who are looking for Practices in Accounting, Introduction to Accounting, and Cost Accounting. Sampling technique in this study used purposive sampling technique. The analytical method used is Simple Linear Regression with analysis tools using SPSS. Practicum based learning can improve the effectiveness of learning for accounting students.Keywords: practicum learning, learning effectiveness